Density functional calculations on actinide compounds: Survey of recent progress and application to [UO2X4]2− (X=F, Cl, OH) and AnF6 (An=U, Np, Pu) - Schreckenbach, Georg; Hay, P. Jeffrey; Martin, Richard L. (Journal of computational chemistry, 1999)
The subject of this article, the application of density functional theory (DFT) to molecular systems containing actinide elements, is discussed in two parts. In the first part, a survey is given of DFT applications on actinide‐containing molecules. Various methodological developments are reviewed, including, among others, new relativistic effective core potentials (ECP), and newly developed stable relativistic DFT methods. Actual DFT calculations of actinide molecular systems are discussed, covering the time from about 1991 to the present. In the second part, two different DFT‐based relativistic methods are applied to some actinide molecules. These are ECPs and the quasirelativistic (QR) method. Systems studied include actinide hexafluorides AnF6 (An=U, Np, Pu) and uranyl (VI) anions [UO2X4]2− (X=OH, F, Cl). Calculated geometries and vibrational frequencies are discussed and compared with experiment. The two relativistic methods have been combined with the BLYP and B3LYP density functionals. The ECP‐B3LYP and QR‐BLYP approaches gave the best bond lengths and frequencies. The existence of stable structures with a bent uranyl bond (“cis‐uranyl”) is predicted for all three [UO2X4]2− ions. ECP‐B3LYP predicts the following order for the stability of the “cis” conformers of [UO2X4]2− (relative to the respective global energy minimum): OH>F>Cl with the “cis”‐[UO2Cl4]2− being least stable. The article concludes with a discussion of future directions for the application of DFT to the f‐block chemistry. © 1999 John Wiley & Sons, Inc. J Comput Chem 20: 70–90, 1999